Agrarian Reform as a Solution to Overcome Land Mafia in The Indonesian Agrarian Legal System - Rollys Suriani; Evy Indriasari; Vegitya Ramadhani Putri; Loso Judijanto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Land mafia has become a serious issue within Indonesia's agrarian system, threatening both justice and legal certainty in land affairs. Practices involving the manipulation of land certificates, illegal land occupation, and collusion between corrupt officials and certain parties have caused significant harm to the public and hindered national development. This study employs a normative legal approach with descriptive analysis to examine the role of agrarian reform as a strategic solution to combat land mafia practices. The findings indicate that agrarian reform through land redistribution, asset legalization, and institutional strengthening can foster a more just and transparent land administration system. A comprehensive implementation of agrarian reform can disrupt the chain of land mafia operations by simplifying administrative procedures, digitizing land information systems, and enhancing oversight mechanisms. Furthermore, agrarian reform contributes to improving farmers' welfare, reducing land ownership inequality, and strengthening national food security. This study recommends the need for strong political commitment, effective inter-agency coordination, and active public participation in implementing agrarian reform. Strict law enforcement against land mafia actors and the development of an integrated land information system are key to the success of agrarian reform in establishing clean and accountable land governance.